A literature review on transformative impacts of blockchain technology on manufacturing management and industrial engineering practices - Dharmendra Hariyani; Poonam Hariyani; Sanjeev Mishra; Milind Kumar Sharma (Green Technologies and Sustainability)
As business performance increasingly depends on decentralized, tamper-proof records to manage transactions and data flows, adopting blockchain technology (BCT) is becoming crucial for remaining competitive in the digital and globalized economy. This review aims to explore the transformative impact of BCT on manufacturing management and industrial engineering practices, particularly in areas like transparency, decision-making, operational efficiency, and trust. Through an extensive review of 480 peer-reviewed papers retrieved from the Scopus database, using the keyword search “blockchain” and “management” or (“manufacturing” or “industrial engineering” or “service” or “supply chain” or “organization”) within the title, abstract, and keywords, this study highlights BCT’s ability to revolutionize supply chain management by providing real-time traceability, automating processes through smart contracts, and ensuring sustainability and compliance. The study finds that BCT significantly enhances management and industrial engineering by improving supply chain transparency, automating operations with smart contracts, and ensuring quality and sustainability. Key findings reveal its effectiveness in improving data security, risk management, and intellectual property protection, alongside optimizing inventory control and customer satisfaction. Moreover, the study identifies innovative applications of BCT in integrating digital technologies such as IoT within Industry 4.0 frameworks, enabling smarter and more resilient manufacturing systems. By addressing challenges such as scalability, regulatory uncertainty, and interoperability, this review offers a roadmap for organizations to adopt BCT effectively. The novelty of the study lies in its comprehensive analysis of BCT’s dual potential, i.e., bridging operational gaps and fostering strategic alignment while providing actionable insights for practitioners to leverage its benefits across diverse industrial applications. This paper serves as a foundational guide to understanding BCT’s role in driving sustainable and competitive growth in modern manufacturing ecosystems.